Chandra X-ray observations of the hyper-luminous infrared galaxy IRAS F15307+3252. Issue 2 (28th September 2016) - Hlavacek-Larrondo, J.; Gandhi, P.; Hogan, M. T.; Gendron-Marsolais, M.-L.; Edge, A. C.; Fabian, A. C.; Russell, H. R.; Iwasawa, K.; Mezcua, M.
Abstract: Hyper-luminous infrared galaxies (HyLIRGs) lie at the extreme luminosity end of the IR galaxy population with L IR  > 10 13  L⊙ . They are thought to be closer counterparts of the more distant sub-millimeter galaxies, and should therefore be optimal targets to study the most massive systems in formation. We present deep Chandra observations of IRAS F15307+3252 (100 ks), a classical HyLIRG located at z = 0.93 and hosting a radio-loud AGN ( L 1.4 GHz  ∼ 3.5 × 10 25 W Hz −1 ). The Chandra images reveal the presence of extended ( r  = 160 kpc), asymmetric X-ray emission in the soft 0.3–2.0 keV band that has no radio counterpart. We therefore argue that the emission is of thermal origin originating from a hot intragroup or intracluster medium virializing in the potential. We find that the temperature (∼2 keV) and bolometric X-ray luminosity (∼3 × 10 43  erg s −1 ) of the gas follow the expected L X-ray – T correlation for groups and clusters, and that the gas has a remarkably short cooling time of 1.2 Gyr. In addition, VLA radio observations reveal that the galaxy hosts an unresolved compact steep-spectrum (CSS) source, most likely indicating the presence of a young radio source similar to 3C186. We also confirm that the nucleus is dominated by a redshifted 6.4 keV Fe Kα line, strongly suggesting that the AGN is Compton-thick. Finally, Hubble images reveal an overdensity of galaxies and sub-structure in the galaxy that correlates with soft X-ray emission. This could be a snapshot view of on-going groupings expected in a growing cluster environment. IRAS F15307+3252 might therefore be a rare example of a group in the process of transforming into a cluster.